Optimalisasi Kerjasama Tripartit Pengelolaan Tandem Paralayang di Site Wisata Tlogo Terbinpotdirga Paralayang FASI Jawa Tengah - Sahri, Sahri; Sugiharto, Sugiharto; Indardi, Nanang; Aristiyanto, Aristiyanto (UNIVERSITAS NGUDI WALUYO, 2022)
This community service is intended to meet the expectations of partners in the development of Tandem Paragliding tourism management, especially those included in the TerBinPotDirga (Dirgantara Potential Development Territory) Pordirga Paragliding FASI Central Java which is currently still running independently and is not efficient in managing tourist areas. This becomes a burden for managers and faces counter-productive conditions in the form of high-cost tourism services that burden service users, and have a direct impact, namely; sluggish and lonely visitors. Cooperation between institutions in Tourism Village Communities in Sports Tourism Areas into joint management known as Tripartite between Tourism Village Communities, Perhutani and the Tourism Office is a solution to solve problems faced by Tourism Village Communities or called Tripartite cooperation. The form of activity is socialization, education, and assistance to participants, namely the Tlogo Tourism Village community, through training with the following materials: Socialization on Organizational Communication Forums, Tripartite management education, Introduction to Aerospace Sports Tourism Service SOPs, and Paragliding Site Determination Simulations. The results of the service are 1) increasing knowledge of communication forums, 2) increasing tripartite management, 3) increasing knowledge of tourist service SOPs, and 4) increasing understanding of determining paragliding sites. So it can be concluded that the optimization of tripartite cooperation in the management of tandem paragliding has an impact on increasing the knowledge, understanding, and ability of Service Partners in managing Aerospace Sports Tourism in the Tlogo tourist area, Wonosobo Regency.ABSTRAKPengabdian kepada masyarakat ini ditujukan untuk memenuhi harapan mitra dalam pengembangan management wisata Tandem Paralayang khususnya yang termasuk dalam TerBinPotDirga (Teritorial Pembinaan Potensi Dirgantara) Pordirga Paralayang FASI Jawa Tengah yang saat ini dirasa masih berjalan sendiri-sendiri dan tidak efisien dalam pengelolaan Kawasan Wisata. Hal ini menjadi beban bagi pengelola dan menghadapi keadaan kontra produktif berupa Layanan Wisata dengan biaya tinggi yang memberatkan pengguna layanan, dan berdampak secara langsung yakni; lesu dan sepinya pengunjung. Kerjasama antara lembaga pada Masyarakat Desa Wisata di Kawasan Wisata Olahraga ke dalam Management bersama yang dikenal dengan istilah Tripartit antara Masyarakat Desa Wisata, Perhutani dan Dinas Kepariwisataan menjadi solusi untuk memecahkan masalah yang dihadapi oleh Masyarakat Desa Wisata atau disebut kerjasama Tripartit. Bentuk kegiatannya adalah sosialisasi, edukasi, dan pendampingan kepada peserta yaitu masyarakat Desa Wisata Tlogo, melalui pelatihan dengan materi: Sosialisasi tentang Forum Komunikasi Organisasi, edukasi manajemen Tripartit, Pengenalan SOP Pelayanan Wisata Olahraga Dirgantara, dan Simulasi Penentuan Site Paralayang. Hasil pengabdian adalah 1) meningkatnya pengetahuan forum komunikasi, 2) meningkatnya pengelolaan secara tripartit, 3) meningkatnya pengetahuan SOP pelayanan wisata, 4) meningkatnya pemahaman penentuan site paralayang. Sehingga dapat disimpulkan bahwa optimalisasi Kerjasama tripartit pengelolaan tandem paralayang berdampak pada meningkatnya pengetahuan, pemahaman dan kemampuan Mitra Pengabdian dalam mengelola Wisata Olahraga Dirgantara di kawasan wisata Tlogo Kabupaten Wonosobo.